A review of the non-avian theropod track record and the implications for the Ontogenetic Niche Shift model - Lockley, Martin G.; Xing, Lida (Earth-science reviews, 2021)
Many Mesozoic formations have yielded substantial dinosaur dominated ichnofaunas, which help characterize coeval communities. When compared with dinosaurian skeletal data (faunal lists) from the same and /or coeval deposits, the completeness and diversity of trace and body fossil records may be shown to be of equal or quite different value for paleoecological analysis and interpretation. The size frequency distribution for >1,170 trackways from 17 theropod dominated Late Triassic-Cretaceous tracksites from North America and China is compared to the data used from the skeletal record to test the Ontogenetic Niche Shift (ONS) model. While track and body fossil databases are different in some regards, they are similar in others, notably in providing coherent size frequency data and useful taxonomic/ichnotaxonomic diversity estimates on a formation by formation or site by site basis. The cumulative, ichnological size frequency data, can be compared with the small, intermediate, and large or megatheropod body mass categories (<100, 100‐1000 and > 1000 kg) used in ONS analysis, and supports the conclusion that ~50%, 31% and 19% respectively of the track sample fall into these three categories. Thus, theropod track abundance is inversely proportional to size. Despite the small proportion of megatheropods track data reveals an increase in the maximum size of theropods through the Mesozoic.